OR22-06 Bone Outcomes Following Sleeve Gastrectomy in Adolescents and Young Adults with Obesity Versus Non-Surgical Controls - Misra, Madhusmita (J Endocr Soc, 2020)
Background: Sleeve gastrectomy is the most commonly performed weight loss surgery in adolescents with moderate-to-severe obesity. While studies in adults have reported on the deleterious effects of gastric bypass surgery on bone structure and strength estimates, data are lacking for the impact of sleeve gastrectomy on these measures in adolescents. Objective: To evaluate the impact of sleeve gastrectomy on bone outcomes in adolescents and young adults over 12 months using dual energy x-ray absorptiometry (DXA) and high resolution peripheral quantitative computed tomography (HRpQCT). Participants and Methods: We enrolled 33 youth 14-22 years old with moderate to severe obesity; 17 underwent sleeve gastrectomy and 16 were followed without surgery. DXA was used to assess areal bone mineral density (aBMD). HRpQCT was used to assess bone geometry, microarchitecture and volumetric BMD (vBMD) and finite element analysis to assess strength estimates (stiffness and failure load) at the distal tibia and distal radius at baseline and 12 months. 25(OH) vitamin D (25OHD) levels were obtained at baseline and follow-up. Results: The surgical group lost 28.2% of total body weight compared to 1.4% in the non-surgical group. The groups did not differ for changes in 25OHD levels (P=0.181). After controlling for age and sex, compared to the non-surgical group, the surgical group had reductions in aBMD Z-scores at the femoral neck and total hip (p≤ 0.0005). At the distal tibia, there were reductions in cortical thickness and trabecular number, and increases in trabecular separation and cortical vBMD, without changes in strength estimates in the surgical group vs. controls (p≤0.043). Changes were less marked at the distal radius. While sleeve gastrectomy resulted in deleterious effects on most bone parameters, there was an increase in cortical vBMD at both sites, possibly from a decrease in cortical porosity. Most differences were attenuated after adjusting for changes in BMI over 12 months. Conclusions: Over 12 months, weight loss associated with sleeve gastrectomy in adolescents had deleterious effects on areal BMD, bone geometry and trabecular microarchitecture at weight-bearing sites. However, strength estimates did not decrease, possibly because of a simultaneous increase in cortical volumetric BMD. Additional research is necessary to determine the relative contribution(s) of weight loss and the metabolic effects of surgery, and whether the observed effects on bone stabilize or progress over time.